The perceived value-added of venture capital investors: Evidence from Finnish biotechnology industry - Mari Maunula (The Research Institute of the Finnish Economy (ETLA), 2006)
This study focuses on the non-financial value-added of venture capital investors (VCs) as perceived by the CEOs of Finnish biotechnology companies. It pays attention to differences in the value-added between informal venture capitalists, private sector venture capitalists and public sector venture capital organizations. In addition, this study pays attention to value-adding mechanisms which venture capitalists use in developing their portfolio companies and factors which influence the perceived valueadded. In general, venture capitalists in Finnish biotechnology companies were found to be rather active hands-on investors, especially in terms of frequent contacts. In addition, their non-financial support was in most cases perceived as important for the success of the Finnish biotechnology companies. The VCs provide value-added indirectly through screening and signaling, and directly through monitoring and providing non-financial support in variety of business areas, for example, in strategic planning and in obtaining additional financing. The value-adding of the VCs was found not to be merely vested in the VCs role in the investee's board of directors, as the VCs were found rather often to be in contact with their investee companies outside the board meetings. The valueadding profile of each VC type was found to differ somewhat from one another. Of all VC types, informal VCs were perceived to provide value-added the most and were the most active in other respects. The public sector VCs stood out as most active providers of indirect value-added through signaling, while private sector VCs were characterized by being actively involved in implementing proper corporate governance. As predicted, the perceived value-added was found to be greater when the relationship with between the CEO and the lead VC was close and there were no tensions inside the investee company resulting from the involvement of VC. The results showed also that short experience of the CEO in investee company's industry increased the perceived value-added.
Keywords: G24; L65; M13; 330; Venture Capital; Biotechnology; Biotechnische Industrie; Risikokapital; Betriebliche Wertschöpfung; Unternehmensplanung; Finnland